2021
DOI: 10.1155/2021/1977388
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Different Types of Red-Light Running Behaviors among Urban e-Bike Rider Mixed Groups

Abstract: The red-light running (RLR) behaviors of urban mixed e-bike groups (delivery and ordinary e-bike) have become the main cause of traffic accidents at signalized intersections. The primary purpose of this study is to identify influencing factors of e-bike riders’ RLR behaviors, focusing on the role of delivery e-bike riders in mixed e-bike rider groups. Crossing behaviors of 4,180 e-bike samples (2006 delivery e-bikes and 2174 ordinary e-bikes) at signalized intersections are observed in Xi’an, China. The random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…With the aim of enhancing the enforcement of wearing helmets for bicyclists and e-bike riders for some trips, helmet laws and related regulations have been supported by previous studies [ 19 , 54 , 55 , 56 ]. For instance, a study by Dong et al (2021) [ 52 ] found that traffic enforcement has a more powerful inhibiting effect on the aggressive driving behaviors of food delivery riders.…”
Section: Literature Reviewmentioning
confidence: 79%
“…With the aim of enhancing the enforcement of wearing helmets for bicyclists and e-bike riders for some trips, helmet laws and related regulations have been supported by previous studies [ 19 , 54 , 55 , 56 ]. For instance, a study by Dong et al (2021) [ 52 ] found that traffic enforcement has a more powerful inhibiting effect on the aggressive driving behaviors of food delivery riders.…”
Section: Literature Reviewmentioning
confidence: 79%
“…The biggest risk of running red lights is colliding with the intersecting motor vehicles, leading to angle collisions, which are extremely destructive. The red-light-running behaviors of e-bikes, including both food delivery e-bikes and ordinary e-bikes, have become the main cause of traffic accidents at signalized intersections in China [32]. Zhang et al [33] collected 3335 samples at four signalized intersections in Xi'an, China, and found that FDRs were more likely to run red lights than ordinary e-bike riders.…”
Section: Riding Safety Attitudesmentioning
confidence: 99%
“…However, this could also worsen traffic safety risks on mixed-use roads. Incidents such as running red lights, speeding, and hit-and-run occurrences have become increasingly frequent [2][3][4]. Data from the National Bureau of Statistics indicates that in 2021 there were a total of 35,141 traffic accidents involving TNVs nationwide [5].…”
Section: Introductionmentioning
confidence: 99%